Intracerebroventricular Administration of 192IgG-Saporin Alters Expression of Microglia-Associated Genes in the Dorsal But Not Ventral Hippocampus - Dobryakova, Yulia V.; Kasianov, Artem; Zaichenko, Maria I.; Stepanichev, Mikhail Y.; Chesnokova, Ekaterina A.; Kolosov, Petr M.; Markevich, Vladimir A.; Bolshakov, Alexey P. (Frontiers in Molecular Neuroscience, 2018)
One of important aspects of development of Alzheimer’s disease is degeneration of septal cholinergic neurons that innervate the hippocampus. We took advantage of widely used model of cholinergic deficit in the hippocampus, intracerebroventricular administration of 192IgG-saporin, to analyze the postponed consequences of cholinergic deficit in different parts of the hippocampus. We studied effects of the immunotoxin on the behavior of rats and gene expression in the dorsal and ventral hippocampus using RNA-seq approach. We found that under normal conditions dorsal and ventral parts of the hippocampus differ in the expression of 1129 protein-coding genes and 49 non-coding RNAs and do not differ in the expression of 10 microRNAs, which were detected in both parts of the hippocampus. 192IgG-saporin-induced degeneration of cholinergic septal neurons did not affect rat behavior in open field, T-maze, and passive avoidance task but impaired memory retention in Morris water maze. To analyze 192Ig-saporin-induced changes in the gene expression, we formed the following groups of genes: genes expressed exclusively in certain cell types (neurons, astrocytes, microglia, oligodendrocytes, and vascular cells) and, among universally expressed genes, a group of genes that encode ribosome-forming proteins. For all groups of genes, the alterations in the gene expression produced by the immunotoxin were stronger in the dorsal as compared to the ventral hippocampus. We found that, among groups of universally expressed genes, 192IgG-saporin increased the expression of ribosome-forming proteins in both dorsal and ventral hippocampus. 192IgG-saporin also strongly upregulated expression of microglia-specific genes only in the dorsal hippocampus. A subset of affected microglial genes comprised genes associated with inflammation, however, did not include genes related to acute inflammation such as interleukins-1b, -6,-15 and -18 as well as TNF. The expression of other cell-specific genes (genes specific for neurons, astrocytes, oligodendrocytes, and vascular cells) was unaffected.. The data obtained suggest that disturbance of memory-associated behavior after administration of 192IgG-saporin is associated with upregulation of microglia-associated genes in the dorsal but not ventral hippocampus.